Pemgaruh Ketepatan Pemberian Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan - Yuni Wahyuni; Juhandi (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2022)
This study aims to examine and analyze the effect of compensation on employee performance, the effect of work motivation on employee performance, the effect of compensation and motivation on performance. The type method in this study uses quantitative methods as causality, which is a study to determine the relationship/influence of independent variables on variables without making additional changes or manipulation of existing data. The population is 367 employees and the sample used in this study is the employees of PT. Parkland World Indonesia Plant 2 Quality Improvement Production Division Cikande Serang which employs 79 employees using the slovin formula. The sampling technique in this study uses Incidental Sampling. The results showed that there was a positive and significant influence on employee performance compensation with value. There is a positive and significant effect of work motivation on employee performance. There is a positive and significant effect of compensation and motivation together on employee performance at PT. Parkland World Indonesia Plant 2 Production Quality Improvement Section. To be able to improve employee performance can be done by offering compensation and increasing employee motivation.